ANALISIS GAYA BELAJAR SISWA KELAS XI JURUSAN IPA DENGAN SISWA JURUSAN IPS DI SMA - Fatimah Setiani; Agus Heriyanto; Siti Aisah (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2018)
To understand the importance of learning styles have because in reality that students learn in his preferred learning style will certainly giving out good results. This study aims to determine trends in student learning styles Xl class majoring in science and social studies department at the high school. The method in this research using descriptive method, the number of population in this study are all high school students are students of class XI as many as 306 students. The samples in the study is proportionate random sampling technique, with the number of 78 students, who captured 25% of the total population. The research instrument used a questionnaire with a scale of psychology. Data analysis techniques that are used is descriptive analysis with formula persentase.Uji validity of using product moment correlation formula. Based on the results of descriptive analysis by percentage, obtained no learning style class XI student majoring in science tend to have a visual learning style amounted to 37.51%, which the Social Sciences has a visual learning style amounted to 38.83%. Thus the learning styles of students majoring in science class XI students majoring in social studies in high school had the same tend divisual.